Testosterone, cortisol, and nocturnal heart rate variability in relation to training load in endurance training - Harjula, Fanny (2024)
The purpose of this master’s thesis was to determine whether salivary cortisol and testosterone levels have a difference between low (LT) and high (HT) 4-day training period. In addition, heart rate variability (HRV) between the same training periods was examined, and whether there was a relationship between changes in hormonal values and HRV. The aim was to determine whether salivary testosterone and cortisol levels could be used to assess the training load of endurance athletes.